Molecular biology of the gene (Pearson, Cummings, 2008)
Molecular Biology of the Gene retains the distinctive character of earlier editions that has made it the most widely used book in molecular biology. Twenty-two concise chapters, co-authored by six highly respected biologists, provide current, authoritative coverage of an exciting, fast-changing discipline.